The History of Ideas of Downscaling—From Synoptic Dynamics and Spatial Interpolation - von Storch, Hans; Zorita, Eduardo (Frontiers in Environmental Science, 2019)
The history of ideas, which lead to the now matured concept of empirical downscaling, with various technical procedures, is rooted in two concepts, that of synoptic climatology and that of spatial interpolation in a phase space. In the former case, the basic idea is to estimate from a synoptic weather map the regional details, and to assemble these details into a regional climatology. In the other approach, a shortcut is made, in that samples of (monthly, seasonal or annual) large-scale dynamical statistics (i.e., climate) are linked to a sample of local statistics of some variables of interest.